Cultivation of candida utilis on cassava peel hydrolysates for single- cell protein production. (2012)
"The growth of Candida utilis NRRL Y-1084 in acid and enzymatic hydrolysates of cassava peel and on glucose in a mineral salts medium was investigated in aerobic submerged cultivation. Kinetic and stoichiometric parameters for growth were determined. The cardinal temperatures of this yeast strain were 14 °C, 33 °C and 41 °C. C. utilis exhibited no absolute requirement for growth factors, although its maximum specific growth rate (μmax) was higher in the mineral salts medium with yeast extract than without, but its biomass yield coefficient (Yx/s) did not differ much in these two media. In the enzymatic hydrolysate, its Yx/s value on sugar was 0.44 with a μmax of 0.35 h-1, whereas the corresponding values were 0.52 and 0.48 h-1 in the acid hydrolysate and 0.50 and 0.37 h-1 in the mineral salts medium without yeast extract. The crude protein content of biomass grown in the glucose medium and the acid and enzymatic hydrolysates were 47.5%, 49.1% and 56.7%, respectively. The amino acid profile of the yeast biomass compared favourably with the FAO standard. Cassava peel hydrolysate has potential as a cheap carbohydrate feedstock for the production of yeast single cell protein by using C. utilis. "